Travestis e organizações: perspectivas das Relações Públicas na construção de espaços organizacionais inclusivos - Teixeira, Guilherme Lopes [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
The objective of this study is to discuss and reflect on the role of public relations in the inclusion of transvestites in the organizational environment, since these are excluded from social spaces by various factors - associated with normativity and its constant reinforcement through institutions such as family, church, school and the market - and communication presents itself as a possibility for transformation. In order to generate this reflection, we used theoretical research, guided by gender studies, with the purpose of exploring questions about social construction, prejudice and transphobia and, thus, to create a panorama about the transvestite experience to understand its position of exclusion against the organizations. In addition to exploring communication perceptions regarding diversity and the role of public relations in this process. Considering this survey and the vision of communication as a humanizing factor, this essay results in a reflection on the transformative potential of public relations and the need for the current communicator to promote spaces for dialogue and inclusion within organizations. In addition, some guidelines for building an inclusive environment in organizations are suggested.It ends with inquiries about public relations, as a profession and area of knowledge, about transvestite identities, ie, it is questioned whether public relations is creating spaces for inclusion of transvestite narratives or only contributing to the maintenance of the norm, taking in view of its potential for a more effective positioning in the creation and maintenance of inclusive organizational spaces for diversity. With this essay, it is hoped to cooperate for new visions and criticisms of communication in relation to diversity and transvestite experiences

O objetivo deste estudo é dialogar e refletir sobre o papel das relações públicas na inclusão de travestis no ambiente organizacional, visto que essas são excluídas dos espaços sociais por diversos fatores - associados a normatividade e seu reforço constante por meio de instituições como família, igreja, escola e o mercado - e a comunicação apresenta-se como uma possibilidade de transformação. Para gerar essa reflexão, utilizou-se de pesquisa teórica, norteada por estudos de gênero, com o intuito de explorar questões sobre construção social, preconceito e transfobia e, assim, criar um panorama sobre a vivência travesti para compreender sua posição de exclusão frente às organizações. Além de explorar as percepções comunicacionais frente a diversidade e o papel das relações públicas nesse processo. Considerando esse levantamento e a visão da comunicação como fator de humanização, este ensaio resulta em uma reflexão acerca do potencial transformador das relações públicas e a necessidade do comunicador atual promover espaços de diálogo e inclusão dentro das organizações. Além disso, sugere-se algumas diretrizes para a construção de um ambiente inclusivo nas organizações. Finaliza-se com indagações sobre as relações públicas, enquanto profissão e área de conhecimento, acerca das identidades travestis, ou seja, questiona-se se o relações públicas está criando espaços de inclusão das narrativas travestis ou somente contribuindo para a manutenção da norma, tendo em vista seu potencial para um posicionamento mais efetivo na criação e manutenção de espaços organizacionais inclusivos para a diversidade. Com este ensaio, espera-se cooperar para novas visões e críticas da comunicação em relação a diversidade e as vivências travestis
Keywords: Travestis; Comunicação; Integração social; Relações públicas; Identidade de gênero; Gender